The Impossible Striptease: Nudity in Jean Calvin and Michel de Montaigne - Peterson, Nora Martin (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2014)
This essay examines the writings of Jean Calvin and Michel de Montaigne, two figures not commonly considered together. The article seeks to highlight a certain fascination with nudity, not only in these texts, but in sixteenth-century culture as a whole. Though it is a bodily phenomenon, I argue, representations of nudity are more than skin-deep; they go beyond the capacity of what the body is able to express. Writings about nudity, whether religious or secular, reflect a widespread anxiety about the relationship between truth and representation in early modern discourse. The preoccupation with surfaces in the texts of both writers highlights the continued epistemological crisis in sixteenth-century religion, culture, and writing.